Integrating Climate Risk into Sustainable Financial Strategies for Indonesian Public Companies - Wilestari, Median; Molina (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Many Indonesian public companies focus on meeting sustainability regulations but fail to integrate climate risks into their financial strategies, creating a gap in achieving climate action goals. This study aims to analyze how these companies incorporate climate risks into their financial planning, identify key barriers, and propose practical solutions. A mixed-methods approach was used, combining questionnaires with a scale to measure integration maturity and content analysis of reports from 15 leading companies in the energy, manufacturing, and financial sectors. The findings show that 75% of companies are compliance-focused, only 20% strategically integrate climate risks, and 5% achieve transformational leadership, with barriers isolated teams, unclear regulations, and a lack of practical tools affecting 65-80% of firms. Bank Mandiri and PT Kalbe Farma stand out for using specialized tools to reduce costs and emissions. The study concludes that companies need tailored tools and stronger regulations to move beyond compliance, while management accountants should lead integration efforts to turn climate risks into business opportunities